1994
DOI: 10.1007/bf01221028
|View full text |Cite
|
Sign up to set email alerts
|

Bombesin antagonists inhibit in vitro and in vivo growth of human gastric cancer and binding of bombesin to its receptors

Abstract: We investigated the effect of bombesin/gastrin-releasing peptide (GRP) antagonist RC-3095 and other analogs on the growth of Hs746T human gastric cancer cells implanted in nude mice or cultured in vitro and on the binding of bombesin to its receptors. Nude mice bearing xenografts of the Hs746T cell line received s.c. injections of RC-3095 (10 micrograms twice daily) or the vehicle (control) for 21 days. Administration of antagonist RC-3095 inhibited the growth of Hs746T tumors. Treatment with RC-3095 produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 36 publications
3
64
0
Order By: Relevance
“…Pinski et al (1994d) showed that RC-3095 at 10 77 M concentration inhibited the growth of U-87MG and U-373MG cells in vitro, by approximately 40 and 60% respectively, in the presence of 10 75 M GRP(14 ± 27). Similar experiments on cancer cell lines that respond to bombesin-like peptides, indicated that exposure to low concentrations of GRP(14 ± 27) results in stimulation of growth, while exposure of the same cells to higher concentrations of GRP(14 ± 27) may produce growth inhibition (Qin et al, 1994a;Wang et al, 1996;Kiaris and Schally, unpublished data).…”
mentioning
confidence: 70%
“…Pinski et al (1994d) showed that RC-3095 at 10 77 M concentration inhibited the growth of U-87MG and U-373MG cells in vitro, by approximately 40 and 60% respectively, in the presence of 10 75 M GRP(14 ± 27). Similar experiments on cancer cell lines that respond to bombesin-like peptides, indicated that exposure to low concentrations of GRP(14 ± 27) results in stimulation of growth, while exposure of the same cells to higher concentrations of GRP(14 ± 27) may produce growth inhibition (Qin et al, 1994a;Wang et al, 1996;Kiaris and Schally, unpublished data).…”
mentioning
confidence: 70%
“…BW2258U89 was reported to inhibit small cell lung cancer growth (Moody et al, 1995b) and to inhibit bombesin-stimulated gastrin release in vivo in dogs and rats and blocked the satiety effect of bombesin in rats (Kirkham et al, 1994). An additional series of substituted pseudopeptide analogs with position 14 substitutions in addition to the 13-14 bond have been described and widely used by Schally's group for inhibition of various tumor cell growth (Radulovic et al, 1991a;Cai et al, 1992Cai et al, , 1994Qin et al, 1994Qin et al, , 1995Jungwirth et al, 1998;Bajo et al, 2004). Two analogs with high potency in this group include [D-Phe 6 ,13-14, Tac 14 ]Bn 6 -14 (tac ϭ thiazolidine-4-carboxylic acid) (RC-3950-II) ) (K i 0.078 nM, murine BB 2 receptor) and [D-Tpi 6 ,13-14]bombesin 6 -14 (RC-3095) (K i 0.92 nM, murine BB2 receptor) Qin et al, 1994Qin et al, , 1995.…”
Section: Bb 2 Receptor Expressionmentioning
confidence: 99%
“…An additional series of substituted pseudopeptide analogs with position 14 substitutions in addition to the 13-14 bond have been described and widely used by Schally's group for inhibition of various tumor cell growth (Radulovic et al, 1991a;Cai et al, 1992Cai et al, , 1994Qin et al, 1994Qin et al, , 1995Jungwirth et al, 1998;Bajo et al, 2004). Two analogs with high potency in this group include [D-Phe 6 ,13-14, Tac 14 ]Bn 6 -14 (tac ϭ thiazolidine-4-carboxylic acid) (RC-3950-II) ) (K i 0.078 nM, murine BB 2 receptor) and [D-Tpi 6 ,13-14]bombesin 6 -14 (RC-3095) (K i 0.92 nM, murine BB2 receptor) Qin et al, 1994Qin et al, , 1995. A final group of potent antagonists in this class were synthesized by J. Martínez's group, with the most potent being JMV641 and JMV594 (Azay et al, 1996;Lamharzi et al, 1998).…”
Section: Bb 2 Receptor Expressionmentioning
confidence: 99%
“…Given the ability of the GRP-R to cause the proliferation of human stomach (33)(34)(35) and colon cancer (14-17) cell lines, we next determined whether ectopic receptor expression altered the growth characteristics of transfected NCM460 cells. Nontransfected NCM460 cells were similar to rabbit colonocytes maintained in primary culture insofar as they required a complex defined media for survival (25).…”
Section: Effect Of Grp-r Expression On Ncm460 Cell Proliferationmentioning
confidence: 99%